STUDI EVALUASI JARINGAN DRAINASE JALAN DANAU MANINJAU RAYA KOTA MALANG - Joko Setiono (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2013)
Along with the very rapid growth of urban areas in Indonesia, urban drainage problems is increasing as well. In general, the handling of drainage in many cities in Indonesia still partial, so it does not solve the problem completely flooding and inundation. Changes in land use due to increasing population growth, requires an adequate supply of residential land, the impact of which directly increases the discharge surface runoff will be collected in drainage channels. Sawojajar Housing is one of the biggest housing in the city of Malang, where the housing development, keep a few problems, one of the flood that happened in 2008 and the incidence of every rainy season yaang inundation caused by the drainage capacity is not accommodating discharge runoff, due to changes in land use and waste sludge. From the analysis of the magnitude of the runoff discharge using recent data, the amount of runoff discharge time 2-year anniversary of 1.66 - 2:32 m3/sec and time again for 5 years 2.1 - 4.2 m3/sec. The dimensions of the existing channel is still accommodate runoff discharge is seen from the criteria condition that occurs sub critical flow (flow). Problems that occur in the hydraulic aspects of the meeting Maninjau Jalan channel as a primary channel that is too upright dg channel Maninjau road so no back-flow, water can not get in and not be able to accommodate discharge from the channel Maninjau Road. Keyword: Flow, Drainage, Flood